Real world outcomes in patients with recurrent, advanced, or metastatic endometrial cancer treated with lenvatinib plus pembrolizumab - A. Pawsey; P. Mahalingam; N. Senthivel; A. Ramessur; E. Turnbull; S. Usman; R. Browne; A. Patel; A. Stewart; L. Tookman; N. Counsell; R. Miller; et al. (Опухоли женской репродуктивной системы)
.